2015
DOI: 10.5897/ajb2014.14338
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Sorghum bicolor (L.) Moench landraces from Northwestern Benin as revealed by microsatellite markers

Abstract: The understanding of genetic diversity within local crop varieties constitutes an important step in the preservation of their genetic potential. The objective of this study was to assess the genetic diversity of sorghum (Sorghum bicolor (L.) Moench) cultivated in the Northwest of Benin and to reveal certain fundamental evolutionary mechanisms. A total of 61 accessions of sorghum landraces belonging to the four identified races in Benin were estimated using 20 microsatellite markers. For all the loci analyzed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
2
1
Order By: Relevance
“…The pigmentation is indication of phenolics are known to provide defense against biotic mainly against shoot fly and abiotic stresses in plants (Dixon and Paiva, 1995). Similar studies were reported by Sangwan et al (2005) for panicle compactness and shape of panicle, Elangovan et al (2009) and Missihoun et al (2015) for inflorescence compactness and shape and glume colour (Figure 3).…”
Section: Semicompact Ellipticalsupporting
confidence: 78%
“…The pigmentation is indication of phenolics are known to provide defense against biotic mainly against shoot fly and abiotic stresses in plants (Dixon and Paiva, 1995). Similar studies were reported by Sangwan et al (2005) for panicle compactness and shape of panicle, Elangovan et al (2009) and Missihoun et al (2015) for inflorescence compactness and shape and glume colour (Figure 3).…”
Section: Semicompact Ellipticalsupporting
confidence: 78%
“…Similar findings by Cuevas and Prom ( 2013), and to a certain extent Agrama and Tuinstra (2003) also reported average PIC values 0.78 and 0.622, respectively. However, the observed PIC value is higher than that of Geleta et al (2006), Antoine et al (2015) and Catherine et al (2016) who reported 0.46, 0.33 and 0.49, respectively. This may be the result of low numbers of accessions considered in their studies and sample collections represented are from specific areas of agroecologies.…”
Section: Marker Polymorphismcontrasting
confidence: 65%
“…Qualitative and quantitative studies, in addition to RAPD, AFLP and SSR markers utilized by different scholars also revealed the same amounts of variations among their collections (Ayana and Bekele, 1998;Geleta et al, 2006;Cuevas and Prom, 2013). SSR marker studies from Eritrean, Eastern Kenya, Benin and Zambia collections also showed presence of wide genetic diversity of sorghum bicolor in Africa mainly in Eastern regions (Tesfamichael et al, 2014;Catherine et al, 2016;Antoine et al, 2015;Ng'uni et al, 2011). The existence of imbalanced sorghum races in the sample collections of the different studies from Ethiopia might contribute to the overall observed genetic variation (Cuevas and Prom, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation